2020
DOI: 10.1021/acsphotonics.0c00594
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Dimensional PbS Quantum Dot–InGaZnO Film Heterostructure for Short-Wave Infrared Flat-Panel Imager

Abstract: There is a growing demand for human-eye-invisible short-wave infrared (SWIR) detection due to its potential in applications in areas such as medical diagnostics, environmental monitoring, and night vision. PbS colloidal quantum dots (QDs) are a promising light absorber for SWIR detection. Herein, we report on a PbS QD/InGaZnO (IGZO) heterostructure-based phototransistor and flat-panel imager for human-eye-safe SWIR photodetection and high-resolution imaging. Such hybrid phototransistors show good electrical pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 37 publications
(61 reference statements)
1
21
0
Order By: Relevance
“…To obtain the colored image, each pixel of the image sensor array was measured with the turtle stencil under RGB light that differs from pixel to pixel, respectively. The light stencil projection method was inspired and developed from previous reports 30 , 64 . Lee et al 30 reported a single-pixel imager and the image scanning system with three different light sources (RGB).…”
Section: Methodsmentioning
confidence: 99%
“…To obtain the colored image, each pixel of the image sensor array was measured with the turtle stencil under RGB light that differs from pixel to pixel, respectively. The light stencil projection method was inspired and developed from previous reports 30 , 64 . Lee et al 30 reported a single-pixel imager and the image scanning system with three different light sources (RGB).…”
Section: Methodsmentioning
confidence: 99%
“…Hwang et al reported a PbS‐QD/IGZO‐based hybrid phototransistor and a flat‐panel SWIR imager. [ 139 ] Figure 12j shows a schematic illustration view of the QD/IGZO phototransistor. In this study, two ligands, tetrabutylammonium iodide (TBAI) and ethanedithiol (EDT), which have been widely employed for PbS‐QD‐based devices, were selected.…”
Section: Classification Of Metal Oxide Phototransistors By Absorption Layermentioning
confidence: 99%
“…58,89 IR image sensors can be used in night vision and biomedical diagnostics. 90,91 Visible light image sensors can be used in face recognition and electronic eyes. [92][93][94] UV image sensors can be used in remote sensing and skin condition monitoring.…”
Section: Imaging Systemmentioning
confidence: 99%